Efek Anti Toksik Ekstrak Etanol Kulit Buah Terung Belanda (Studi Pada Ginjal Tikus Wistar Paska Induksi Karagenin) - Agita, Debi; Sudiono, Janti; Trisfilha, Trisfilha (Jurnal Material Kedokteran Gigi, 2023)
Dutch eggplant fruit is traditional medicine, their skin is often wasted because not many people know what it contains. Objective. To know the anti-toxic effect of dutch eggplant peel’s extract post-carrageenin induction on rat’s kidneys. In vivo experiments was divided into 5 groups, negative control group (saline), positive control group (sodium dilcofenac) 7mg/kgBW, and dutch eggplant’s peel extract at doses of 70mg/kgBW, 140mg/kgBW, and 280mg/kgBW. Mice’s buccal submucosa was injected with Caraagenin 1%. After injection, this study did macroscopic and microscopic observations for 24 hours, 48 hours and 72 hours. Results, Dutch eggplant peel’s phytochemical test contains phenolic, flavonoid, tannin, and alkaloid content. At all doses, anti-toxic effect of dutch eggplant peel’s ethanol extract has same healing effectiveness process with 48 hours. In positive control, the kidneys were normal at 48 hours. Meanwhile, the negative control’s healing effectiveness was seen at 72 hours. The anti-toxic effect from dutch eggplant peel’s ethanol extract has effective healing process at all doses in 48 hours post-carrageenin induction, and did not affect rats’ body weight, however with lower intensity than positive control which using dilcofenac, anti-inflammatory drug.